What One Can Know: Fitch’s Argument and Its Consequences - Smokrović, Nenad (Analiza: časopis za kritično misel, 2025)
The paper, motivated by the chapter in Šuster’s book, considers the aspect of the so-called Fitch’s ar-gument (FA) that seriously challenges the verificationist theory. Contrary to Šuster’s view, it is throughout the paper that I’m pursuing the idea that most of the attempts that intend to vindicate verifi-cationism from the grip of Fitch’s argument, including Edgington’s theory, fail in their intention. Con-cerning the attempts to mitigate the effect of Fitch’s argument to verificationism in the framework of classical logic (Eddington as the most important representative), I’m siding with their critics (William-son, Percival) and claim that they fail in their intention. Regarding the attempts to block the effect of Fitch’s argument in the framework of non-classical (intuitionistic, relevant, dialetheist, and so on) log-ic, they do it by introducing principles that invalidate some of the basic classical rules and principles, usually introducing trivial worlds. In that case, the verificationist principle (as well as all inferences included in Fitch’s argument) is vacuously valid, which seems to be unsatisfactory. In any case, there is no decisive evidence that either classical or any of the non-classical approaches can avail the verifi-cationist anything to escape out of the grip of FA.